Bacteria Detection Salmonella sp. in Fish Meatball Products Sold in Some Traditional Markets in Surabaya - Permata Jelita, Chelsea; Mahasri, Gunanti; saputra, Eka (Journal of Marine and Coastal Science, 2023)
Fish meatballs are processed fishery products that use minced fish meat or surimi of at least 40% mixed with flour, and other ingredients if needed, which undergo formation and cooking. In general, fish meat used is for example snapper, grouper and mackerel. This study aims to determine the detection of Salmonella sp. bacteria, fish balls sold in several traditional markets in the city of Surabaya and the calculation of Total Plate Count of processed fish balls circulating in several traditional markets in Surabaya. The research method used is a direct survey for sampling. The sampling location of fish balls was done intentionally or purposive sampling method. Analysis of the data to determine the Total Plate Count of Salmonella sp. bacteria in fish balls in several traditional markets in Surabaya, which is displayedin tabular form. The results showed that the detection of Salmonella sp. bacteria was positive in two samples out of a total of 10 samples. The results of the Total Plate Count (TPC) test for Salmonella sp. in the two different samples in the same area of West Surabaya, it was 2x105 CFU/gr for the first sample and 1x103 CFU/gr for the second sample.